2008
DOI: 10.1055/s-0030-1247821
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Outcome of Primary Tumors of the Patella

Abstract: Demographics, pathology, and outcomes of 7 patellar tumors, including 2 giant cell tumors, 2 chondroblastomas, 1 osteoid osteoma, 1 osteitis fibrosa cystica, and 1 case of myelomatous infiltration, are described. Five male and 2 female patients with a mean age of 42.5 years were followed for an average of 3.5 years. Anterior knee pain was the main presenting symptom. Two patients presented with pathologic fracture. One patient with chondroblastoma underwent curettage only; the second patient underwent curettag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 6 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…Only a few studies have reported these lesions, and most are case reports. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The most frequent tumors in this location are giant cell tumor, chondroblastoma, and aneurysmal bone cyst. 7,8 Chondroblastoma accounts for 1% to 3% of all primary benign bone tumors and 22% of benign bone tumors in the patella.…”
Section: Chondroblastoma Of the Patella With Aneurysmal Bone Cystmentioning
confidence: 99%
“…Only a few studies have reported these lesions, and most are case reports. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The most frequent tumors in this location are giant cell tumor, chondroblastoma, and aneurysmal bone cyst. 7,8 Chondroblastoma accounts for 1% to 3% of all primary benign bone tumors and 22% of benign bone tumors in the patella.…”
Section: Chondroblastoma Of the Patella With Aneurysmal Bone Cystmentioning
confidence: 99%
“…Chondroblastomas and giant cell tumors form the most common tumors of the patella [12][13][14] . This is probably due to the similarity in the ossification of the patella with that of the epiphysis of long bones [11] . There are reports of tumors like osteoid osteoma, osteoblastoma, spindle cell sarcoma, osteitisfibrosacystica, aneurysmal bone cyst and myelomatous infiltration arising from the patella [15][16][17][18][19][20] .…”
Section: Discussionmentioning
confidence: 98%
“…However, documentation of ES of patella in the English medical literature is lacking. Chronic anterior knee pain is the most common presenting feature in patients with patellar tumors [11] . The prognosis for patellar tumors is good even though most of the cases appear late, as majority of the tumors are benign [11] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations